Toward Efficient Wound Management: Bioinspired Microfluidic and Microneedle Patch. Issue 3 (4th December 2022) - Wang, Yuqiu; Gao, Bingbing; He, Bingfang
Abstract: Microneedle (MN) patches hold demonstrated prospects in intelligent wound management. Herein, inspired by the highly folded structure of insect wings, a three‐dimensional (3D) origami MN patch with superfine miniature needle structures, microfluidic channels, and multiple functions was reported to detect biomarkers, release drugs controllably and monitor motions to facilitate wound healing. By simply replicating the pre‐stretched silicone rubber (Ecoflex) molds patterned by a laser engraving machine, the superfine structure MN patch with microfluidic channels was obtained from the restored molds. The bioinspired origami structure endows the MN patch with a high degree of functional integration, including microfluidic channels and electrocircuits. The microfluidic channels combined with the pH value and glucose concentration indicators enable the patch with the capability of biomarker sensing detection. Porous structures, a temperature‐responsive hydrogel, and a photothermal‐sensitive agent are utilized to form a controllable drug release system on the MN patch. Meanwhile, MXene electrocircuits were printed on the MN patch for motion sensing. In addition, the ability of the MN patch to accelerate wound healing was demonstrated by a mouse model experiment with full‐thickness skin wounds. These results indicate that the multifunctional 3D origami MN patch is a valuable intelligent strategy for wound management. Abstract : Highly folded insect wings‐inspired three‐dimensional (3D) origami microneedle (MN) patch with a superfine needle tip structure, microfluidic channels, biomarker detection, controllable drug release, and motion monitoring are fabricated by replicating stretched negative molds. The multifunctional MN patch presents outstanding applicability for promoting the wound healing process.